Model of pipeline vibrations during unauthorized exposure - A. A. Fedotov; R. A. Akhmedzhanov; A. A. Pyatkov (Омский научный вестник, 2019)
The article presents a model for calculating elastic vibrations recorded on the surface of a pipeline as a result of impact. The use of an empirical refinement characteristic together with an analytical expression made it possible to synthesize a vibroacoustic signal corresponding to unauthorized impact to the pipeline. The adequacy of the proposed solution is estimated by comparing the calculated signal with the empirical one. Models can be used to develop and test algorithms for identifying impacts on the pipeline.